Biological, toxicological and molecular docking evaluations of isoxazoline-thiazolidine-2, 4-dione analogues as new class of anti-hyperglycemic agents. Issue 3 (11th February 2023) - Fettach, Saad; Thari, Fatima Zahra; Hafidi, Zakaria; Karrouchi, Khalid; Bouathmany, Kaoutar; Cherrah, Yahia; El Achouri, Mohammed; Benbacer, Laila; El Mzibri, Mohammed; Sefrioui, Hassan; Bougrin, Khalid; Faouzi, My El Abbes
Abstract: In this work, three isoxazoline-thiazolidine-2, 4-dione derivatives were synthesized and characterized by FT-IR, 1 H-NMR, 13 C-NMR and ESI-MS spectrometry. All compounds have been investigated for their α-amylase and α-glucosidase inhibitory activities. In vitro enzymatic evaluation revealed that all compounds were inhibitory potent against α-glucosidase with IC50 values varied from 40.67 ± 1.81 to 92.54 ± 0.43 µM, and α-amylase with IC50 in the range of 07.01 ± 0.02 to 75.10 ± 1.06 µM. One of the tested compounds were found to be more potent inhibitor compared to other compounds and standard drug Acarbose (IC50 glucosidase = 97.12 ± 0.35 µM and IC50 amylase = 2.97 ± 0.01 μM). All compounds were then evaluated for their acute toxicity in vivo and shown their safety at a high dose with LD > 2000mg/kg BW. A cell-based toxicity evaluation was performed to determine the safety of compounds on liver cells, using the MTT assay against HepG2 cells, and the results shown that all compounds have non-toxic impact against cell viability and proliferation compared to reference drug (Pioglitazone). Furthermore, the molecular homology analysis, SAR and the molecular binding properties of compound with the active site of α-amylase and α-glucosidase were confirmed through computational analysis. This study has identified the inhibitory potential of a new class of synthesized isoxazoline-thiazolidine-2, 4-dione derivatives in controlling both hyperglycemia and type 2 diabetes mellitus without any hepatic toxicity. Communicated by Ramaswamy H. Sarma